The biogenesis of erythropoietin during inflammation - Leng, Henry Martin John (Division of Clinical Pharmacology, 2018)
Anaemia frequently accompanies chronic inflammatory diseases like rheumatoid arthritis and cancer. It is postulated to result primarily from the suppression of erythropoiesis by inflammatory cytokines. A contributing factor could be the inhibition of erythropoietin synthesis which may also be mediated by cytokines. Erythropoietin is the hormone which regulates erythropoiesis. The aims of this project were to investigate whether cytokines can indeed suppress erythropoietin production, and to determine whether the erythropoietin response in experimental models of acute and chronic inflammation was appropriate for the associated anaemia. Macrophage-conditioned medium, interleukin-1β, interleukin-6, tumour necrosis factor-α, and neopterin were assayed for inhibition of erythropoietin synthesis by HepG2 cells in culture. All, except neopterin, effected dose-dependent reductions in the secretion of the hormone. Interleukin-1β and tumour necrosis factor-α down-regulated erythropoietin gene transcription, whereas interleukin-6 inhibited a post-transcriptional process. Rats with acute inflammation developed a mild anaemia which evoked an increase in their serum levels of erythropoietin. The serum erythropoietin levels were optimal, since rats with acute inflammation and severe phenylhydrazine-induced anaemia did not have lower levels of the hormone than controls with a similar degree of anaemia, but without acute inflammation. Erythropoietin is, therefore, not an acute phase reactant. Mice with cancer developed a progressive anaemia which was not due to bone marrow invasion by tumour cells. During the first fourteen days after inoculating them with cancer cells, the mice responded by increasing their serum levels of erythropoietin as the anaemia worsened. The erythropoietin response was appropriate when compared to mice with the same degree of phenylhydrazine-induced anaemia. Erythropoietin levels measured in mice with tumours older than fourteen days were significantly lower than those of control mice with the same degree of experimental anaemia. These animals were very cachectic, suggesting that a blunted erythropoietin response may depend on disease activity.